Covid-19 effects on solid waste management - Pariona-Palomino, Jordy (2022)
The outbreak of the Coronavirus disease Covid-19, has brought with it a series of side effects without precedented especially in the management of solid waste, getting worse in developing countries. The present study is a systematic review of the literature. Of a total of 825 publications from ScienceDirect, Scopus, and Wos, 60 scientific articles and most relevant reports on the effects of Covid-19 on waste management were considered. An exponential behavior in the generation of waste focused on the use of plastic was evidenced. The guidelines issued by international organizations and the main affected countries emphasize the use of PPE, hygiene, disinfection, and labeling of waste, as well as a special management system under these conditions. The literature showed that the impacts of Covid-19 directly affected the processes of segregation, recycling and disposal, product of generation and disposal techniques. The survival time of the virus on the fomites is a few hours and even exceeds seven days, being a problem for management. The challenges that the pandemic brings with it are aimed at developing policies to decentralize management, automation, and the consideration of chemical disinfection and incineration as viable treatment alternatives.